Políticas curriculares e gestão escolar: continuidade ou ruptura em relação aos anos iniciais e anos finais do ensino fundamental? - Frasson, Carine Martins Godoy Torres (2019)
This Master's thesis is part of the Line of Political Research and Management of Basic and Higher Education of the Graduate Program, Professional Master's degree in Public Policy and Educational Management of the Federal University of Santa Maria (UFSM). Its main objective is to investigate the relationship between curricular policies and the organization of the transition between the early and final years stages of elementary school. As specific objectives, we seek: to understand the role of management in relation to the curricular organization; reflect on curricular policies for elementary school; and discuss the relationship between the curricular organization with school performance of the students. The methodology is based on the qualitative approach using the theoretical and methodological assumptions of the case study method. The information collection was performed from the questionnaire conducted with the collaborating teachers of the Pinto Ribas school and Alfredo Lenhart school. Discussions and reflections were based on legislation, guidelines, official documents from the Ministry of Education. The theoretical basis is based on authors such as Leão (2015), Fernandes (2011), Sacristan (2000, 2013), Lebanese (2006, 2012), Arroyo (2000), Moreira and Candau (2007), Pacheco (2008) among others. The analysis was performed based on the recurrence of thematic units that indicated the following categories of analysis: Public Policies and BNCC organization: implementation process; Integration, dialogue, training and transition; Impact, difficulties, maturity. Thus, it was possible to recognize that it is the curricular policies that promote the change in the organization of schools. May these policies interfere to rethink practices, and teachers indicate that there is a need for an organization of times, dialogues, training, resuming research categories. Thus it was understood that as a final product to reflect on the transition from the initial years to the final years a "training proposal" will be proposed to assist the school in the curriculum implementation. The perspective is to produce reflections on the challenges of continuing teacher training based on ongoing policies.